FRI0485 Comparative Study on Adalimumab vs Infliximab for Treatment of Uveitic Cystoid Macular Edema Due To Behcet's Disease. Multicentre Study of 34 Patients. (15th July 2016) - Beltrán-Catalán, E.; Calvo-Rio, V.; Blanco-Alonso, R.; Fernandez, C.; Rodriguez, P.; Hernandez, M.; Herreras, J.M.; Cordero, M.; Mesquida, M.; Adan, A.; Hernandez, M.V.; Diaz-Valle, D.; et al.
Abstract : Objectives: Cystic macular edema (CME) is the most serious complication of uveitis and the most common cause of blindness. Our objective was to compare the efficacy and safety of adalimumab (ADA) vs infliximab (IFX) as the first biological drug in uveitic cystoid macular edema (CME) due to Behçet's disease (BD) during 1 year follow-up. Methods: In a multicentre study of 175 patients with BD and uveitis refractory to conventional therapy, 34 patients had CME, defined by (OCT >300μ) at baseline. IFX (3–5 mg/kg 0, 2, and 6 weeks and then every 4–8 weeks) was used in 12 cases and ADA (40 mg/2 weeks) in 22 cases. The main objective was the absence of CME. Secondary objectives: improvement in visual acuity (VA) (increased AV >20% in at least one of two eyes), inactive anterior chamber inflammation, vitritis, retinitis and retinal vasculitis. A bivariate analysis was performed to compare the response to biological therapy (ADA and IFX). Results: We studied 34 patients (63 affected eyes). No statistically significant baseline differences were observed between both groups (IFX vs ADA) sex (men/women 4/6 vs 11/11; p=0.35), mean age (37.3±10.1 vs 41.5±8.3; p=0.2) HLAB51 positive (70% vs 80.9%; p=0.5), duration of uveitis before anti TNF alpha treatment [median (IQR]; 36 [10–82] vs 33 months [15.5 to 83]; p=0.8), VA (0.4 ± 0.33 vs 0.46±0.29; p=0.44); retinal vasculitis (75% vs 77%; p=0.87); retinitis (46% vs 30%; p=0.2); macular thickening (140.9±410.13 vs 409.46±138.55; p=0.98); combined treatment (58.33% vs 59.1%; p=0.96). We found differences in the presence of cells in the anterior chamber (Median [IQR]; 1 [0–1.2] vs 1 [0–3]; p=0.02) and vitritis (median [IQR], 1 [0–2] vs. 3 [0.5 -3]; p=0.002). Regarding the main objective, the improvement of CME is higher in patients treated with ADA during first month of treatment maintained at a year, although the difference is not statistically significant (table ). With IFX we observed an improvement during the first month of treatment in vitritis, that became inactive, in the disappearance of the anterior chamber cells, and in retinitis and vasculitis that also became inactive. In no case statistically significant differences are reached. When adjusting for duration of illness, age and sex these differences remain. After a year of treatment all patients with retinitis and vasculitis in its baseline improve (ADA and IFX). Conclusions: Our study suggests that ADA and IFX don't show statistically significant differences in treatment of CME due to refractory uveitis in BD after 1 year follow-up. Disclosure of Interest: None declared